Spiritual Intelligence (SI) in the eyes of Muslim academicians: a qualitative exploratory study - Ahmed, Iman Osman Mukhtar; Badrasawi, Kamal J I (2017)
Spiritual intelligence (SI) has various definitions. However, most research has maintained that spiritual intelligence is concerned with the integration of the inner life of mind and spirit with the outer life. It is important for a human being to have a balance between the inner self and the outer life to carry on with their life in the society. Spiritual intelligence and its components have not been thoroughly investigated from Islamic perspective. Hence, this study aims to explore views of Muslim academicians on the concept of spiritual intelligence, its components and inclusion in Muslim education. The qualitative exploratory study used open-ended interviews of two academicians for collecting data. The interviewees were purposefully selected from an Islamic university in Malaysia and they had religious and psychological backgrounds and more than fifteen-year experience in the field of Usulu Eddin (Theological Teaching). In addition, they also had published articles on Spiritual Intelligence in various reputed journals. The thematic analysis of their interviews showed that SI has no distinctive definition and components determined by the Muslim scholars. The respondents have stressed that the SI definitions and components should be based on the main sources of Islamic education (i.e. Quran and Sunnah) and approaches of human personality development. Moreover, they clarified that the Western perspective on IS differs from Islamic perspective. They suggest to include SI in Muslim education system to enhance students’ spirituality. Further qualitative and quantitative studies are recommended to be carried out in order to have a better understanding of SI.